(untitled) (Journal of the College of Basic Education, 2024)
This research aims to identify (the effect of the scale strategy on the achievement and development of visual thinking in Arabic grammar among female students in the second intermediate grade). To achieve this, the researcher chose a sample of (67) female students from the second intermediate grade in (Al-Hawraa Middle School for Girls ) of the Diyala Education Directorate, with (34) female students for the experimental group and (35) female students for the control group. The researcher studied the experimental group by adopting the scale strategy and the control group the traditional method. The researcher rewarded the female students of the two research groups in the variables of chronological age calculated in months and the academic achievement of the mothers and fathers. And the intelligence test, and the visual thinking test. The researcher controlled the extraneous variables that might affect this type of experimental design. After the researcher identified the scientific material that included topics from the Arabic language book scheduled to be taught to female second-year intermediate students for the academic year (2022-2023), the researcher formulated The behavioral objectives of the teaching plans for the subjects reached a final number of (54) behavioral objectives. The researcher prepared model teaching plans for each of the subjects specified for the experiment. In order to measure the achievement and visual thinking among the female students of the two research groups, the researcher prepared two tests, the first a test of achievement and visual thinking. After applying the research tool and analyzing the results obtained by the researcher statistically, the researcher concluded that teaching with the necessity of adopting the scale strategy in achievement and visual thinking is better for the female students of the second intermediate grade compared to the usual method. She recommended the necessity of adopting the scale strategy in teaching the rest of the curriculum vocabulary among the female students of the second intermediate grade, and she suggested The researcher conducted studies similar to the current study in other branches of the Arabic language.